Effects of Organic Agriculture in Structure and Organic Carbon Adsorption at Colloidal Scale in Marginal Olive Groves, Characterized by the Extended DLVO Model - Calero, J.; Plaza, I.; Ontiveros, A.; Aranda, V.; García-Ruiz, R. (Frontiers in Environmental Science, 2022)
Relationship between macroscopic and microscopic behavior of soils is a difficult issue, especially when dealing with complex properties such as structure or carbon sequestration, but it is necessary for a suitable understanding of the agricultural soil quality. In this work, we used the extended-DLVO theory to compute total energy of interaction between particles (kT), of three soils over granodiorites. This parameter allows predicting the tendency to aggregate formation at the colloidal scale, being the basis of soil structure. Furthermore, we characterized the mechanism and adsorption capacity of humic molecules on mineral surfaces, and its influence in the interaction energy, by means of the adsorption isotherms. The aim was to compare first the effects of organic farming on conventionally managed soils and, second, to compare these with a non-cultivated forest soil under Mediterranean climate. When total energies are negative (particle attraction), or positive (particle repulsion) but near 0 kT (< 100 kT), then particle flocculation occurs and the structure at colloidal scale can be developed. Total energy was less in the forest sample and greater in the soil of conventional groves, with intermediate values in organic soil. This indicates a tendency toward particle flocculation and more stability of the structure at colloidal scale in less disturbed soils, agreeing with other soil physical properties such as the total porosity (60%, 41% and 37% in forest, organic and conventional soils, respectively) or the aggregate stability index (0.94, 0.73 and 0.66, respectively), which followed the same trend. Of the three components of the total energy of interaction, the acid-base force was a key factor. This component, related with the electron-donor component of surface free energy, -, yielded a strong attractive force (−150 kT at 3 nm) when calcium solutions were analyzed for the forest soil. This indicates a clear hydrophobic character of this sample. We believe that this hydrophobicity may be explained by the large amount and aliphatic nature of the soil organic matter in the non-cultivated soil, which could be inferred by the larger E4/E6 ratio showed by these soils (4.69, 3.31 and 3.10 in forest, organic and conventional soils, respectively).